1978
DOI: 10.1002/art.1780210202
|View full text |Cite
|
Sign up to set email alerts
|

Familial lupus. family studies of hla and serologic findings

Abstract: HLA profiles in 103 members of 4 separate kindred with multiple occurrence of SLE were compatible with the presence of a disease susceptibility factor linked to HLA or a direct effect of antigens B8, A l l , and B35 on disease expression. Serum ANA was found in 52.9% of consanguineous, 56.5% of nonconsanguineous relatives of SLE probands, and 5% of controls, a finding that suggests the presence of a transmissible agent in the families. By contrast, lymphocytotoxic antibodies were not increased in relatives com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…38 Genetic predisposition plays a crucial role in susceptibility, and environmental exposure can cause epigenetic change 39 or trigger activation of innate and adaptive immune response to induce or accelerate the development of SLE in susceptible individuals. 40 Strong familial aggregation in SLE has been reported [6][7][8][9][10][11][12][13][14][15][16] but, to the best of our knowledge, this is the first populationbased study investigating the familial aggregation of SLE and coaggregation of other autoimmune diseases in first-degree relatives of people with SLE. We found that the first-degree relatives have a 17-fold increased risk of SLE compared with the general population and that genetic relatedness is associated with the magnitude of risk of SLE.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…38 Genetic predisposition plays a crucial role in susceptibility, and environmental exposure can cause epigenetic change 39 or trigger activation of innate and adaptive immune response to induce or accelerate the development of SLE in susceptible individuals. 40 Strong familial aggregation in SLE has been reported [6][7][8][9][10][11][12][13][14][15][16] but, to the best of our knowledge, this is the first populationbased study investigating the familial aggregation of SLE and coaggregation of other autoimmune diseases in first-degree relatives of people with SLE. We found that the first-degree relatives have a 17-fold increased risk of SLE compared with the general population and that genetic relatedness is associated with the magnitude of risk of SLE.…”
Section: Discussionmentioning
confidence: 96%
“…3 Our group estimated that the prevalence of SLE was 0.10% in the United Kingdom 4 and 0.07% in Taiwan. 5 Early family studies [6][7][8][9][10][11][12][13] documented familial aggregation of SLE, and a classic twin study 14 found a 10-fold increased concordance in monozygotic compared with dizygotic twins. Furthermore, SLE has been reported 10,12 to coaggregate with other autoimmune diseases.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Recent reports associated Bw35 with necrotizing cutaneous venulitis (37), nonstreptococcal glomertulonephritis (38) and, in one family with inheritance of many of the clinical features of systemic lupus erythematosus (39). As Cleland et al (39) observed, the relationship of these diseases to HLA-Bwv35 is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is an abundance of evidence to support the potential for a genetic contribution to the disease in these families, from both murine and human studies. Previous studies have examined familial aggregation of SLE in pedigrees containing affected male members (32)(33)(34). The report by Lahita et al (34) describes 4 unique pedigrees containing at least 2 affected male members each.…”
Section: Discussionmentioning
confidence: 99%